1991
DOI: 10.1007/bf01787485
|View full text |Cite
|
Sign up to set email alerts
|

Structure function analysis of theH-2 Ab p gene

Abstract: The gene encoding the H-2 Ap class II beta chain was isolated from a B10.P genomic library and sequenced. This gene was also used to construct transfectants of the CH12 lymphoma clone CH12.LX, which express the Abp gene product in association with the endogenous A alpha k chain. We present here the first report of the complete nucleotide coding sequence of Abp. The predicted amino acid sequence of Abp reveals only five residues different from Abq, four of which are present in the mature peptide. These four ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Subsequent work I performed with Jeffrey Frelinger revealed that B cell class II MHC molecules can deliver one of these T cell-mediated signals (3,4). As a new Assistant Professor at the University of Iowa, my laboratory further characterized class II-mediated signaling pathways (5,(6)(7)(8), and many other laboratories also made important contributions to this topic (reviewed in Ref. 9).…”
mentioning
confidence: 99%
“…Subsequent work I performed with Jeffrey Frelinger revealed that B cell class II MHC molecules can deliver one of these T cell-mediated signals (3,4). As a new Assistant Professor at the University of Iowa, my laboratory further characterized class II-mediated signaling pathways (5,(6)(7)(8), and many other laboratories also made important contributions to this topic (reviewed in Ref. 9).…”
mentioning
confidence: 99%